PTEROCACTUS (CACTACEAE), NUEVO REGISTRO PARA LA FLORA DE CHILE PTEROCACTUS (CACTACEAE), NEW RECORD FOR THE CHILEAN FLORA - Roberto Kiesling (Universidad de Concepción, 2002)
Se menciona el género Pterocactus (Cactaceae) por primera vez para la flora de Chile, representado por P. hickenii Britton & Rose. Además, esta especie, que se conocía sólo del extremo SE de la Patagonia, con las nuevas colecciones amplía su área conocida a toda la meseta patagónica al S de la latitud 43°30' S en Argentina The genus Pterocactus (Cactaceae) is recorded for first time for the flora of Chile, represented by P. hickenii Britton & Rose. Previous to this finding, the distribution of this species had been known only from the SE of Patagonia. The new records extend its geographic range to all of the patagonic plateau south of latitude 43° 30' S in Argentina